INTENSIFICATION OF GLOBALIZATION PROCESSES IN THE INFORMATION ERA - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The main directions of intensification of globalization processes imposed by informatization of various social spheres are investigated in the article. The article substantiates the claim that the usage of information technologies substantially accelerates globalization in the field of economics, finance, science and education, as well as expands the scope of mass culture standards. There are, however, also negative global processes accelerating due to the use of information and communication technologies. Among the negative processes with the worst effects planetary proliferation of terrorism, drugs and weapons of mass destruction are worth mentioning.